2022
DOI: 10.1177/07316844211072529
|View full text |Cite
|
Sign up to set email alerts
|

Blast behaviour of fibre reinforced polymers containing sustainable constituents

Abstract: As the use of more sustainable natural fibres and bio-based resins in fibre reinforced polymers (FRPs) becomes more widespread, their susceptibility to damage due to explosive detonation needs to be evaluated. In this paper, flax and jute FRP panels were blast tested and compared to equivalent mass glass FRP panels. Comparisons were made between flax and glass FRPs manufactured using a synthetic Prime 20 epoxy and a Super Sap epoxy resin containing bio-based raw materials. The transient measurements revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…If a fibre fails along its entire length revealed within the crack flanks, it is rendered dormant in terms of load input. If, on the other hand, the fibre fails along the debond length, it will pull-out (Gabriel et al, 2022). The energy spent as friction at the contact is the pull-out mechanism's input to the energy dissipation capacity of the composite.…”
Section: Fractography Analysismentioning
confidence: 99%
“…If a fibre fails along its entire length revealed within the crack flanks, it is rendered dormant in terms of load input. If, on the other hand, the fibre fails along the debond length, it will pull-out (Gabriel et al, 2022). The energy spent as friction at the contact is the pull-out mechanism's input to the energy dissipation capacity of the composite.…”
Section: Fractography Analysismentioning
confidence: 99%
“…Upon closer scrutiny of the 467 examined documents, only a few studies revealed composites designed explicitly for targeted applications, as outlined in Table 3. Additionally, other studies explored the development of composites for potential applications, including wind turbine blades, 36,37 automobile body parts, [38][39][40] ballistic armour components, 41,42 non-structural building panels, 43,44 pressure vessels, 45 electric circuit boards, 46 and composite film for packaging applications. 47,48…”
Section: Publication Outputmentioning
confidence: 99%